دور تعديل القوة الإنجازيّة للفعل الكلامي في تبليغ محتوى تعليميّ حصّة تعليميّة (فهم المنطوق)– في مرحلة المتوسّط - موساوي, عبد العالي (جامعة الوادي - university of Eloued, 2022)
إنّ دراسة للمُنْجزِ اللّغويّ أثْناء الاسْتِعْمال لا يكون إلّا بِرَبطِ اللّغَة بِكُلّ مَا يُحيط بها أثْنَاءَ عَمَليّة التّلفُظ .ذاك هو صميم التداوليّة التي تهتمّ بِفهْمِ مقْصَدِ المتكلّم عنْد تبليغ هذا المُنْجز الذي يُحْدِثُ تأْثيرًا بيّنا في المتلقّي؛و هذا منْ أهمِّ مَا جادتْ بِهِ نظرِيّة أفْعَال الكَلام التي تُعَدُّ نواة مرْكَزِيّة في الأعمال التّداوليّة .والتي قسّمها أوستين إلى ثلاثة أفعال باعتبارها"كُلُّ مَلْفُوظٍ ينْهضُ عَلَى نِظَامٍ شَكْليٍّ دَلاليّ إِنْجَازيٍّ تَأْثِيرِيّ":فعل القول,الفعل المتضمّن في القوْل(إنْجازي),الفعل النّاتج عن القوْل.والفعل الثّاني هو المقصود من النّظريّة كلّها.لذا اقترح أوسْتين تسْمية الوَظائف اللِّسانِيّة الثّانويّة خلف هذه الأفعال"القوّة الإنجازيّة".هذه الأخِيرَة قدْ يغيّر فيها المتكلّم أو بتصرّف فيها بتعديلٍ ما(قوّة أو إضعافا) حَسْبَ ظُروف إنْتاجِ القوْل.وبمَا أنَّ العَمَليّة التّعليميّة التَّعَلُّميّة تُعْتَبر ميْدانا خِصْباً لعَمليّة التّواصُل؛ كانت هذه الورقة البحثيّة ميدانا إجرائيّا عمليّا لطَرْحِ الإشْكَالِ الآتِي:كَيْف يُسْهِم تعْديل القوّة الإنْجازيّة في إنْجاح العمليّة التواصليّة بيْن المعلّم والمتعلّم؟ داخِل حُجْرة الدّراسة. Studying the linguistic illocutionary during use is only by linking the language to everything that surrounds it during the pronunciation process.That is the heart of pragmatics, which is interested in understanding the speaker's purpose when communicating this illocutionary, which has a clear impact on the recipient.This is one of the most important things about the theory of speech acts, which is consideredas a central nucleus in the pragmatic work. It was divided by Austininto three acts as “every operative based on an influential performative semantic formal system”:locutionary act, illocutionary act, and perlocutionary act. The second act is the purpose of the whole theory. Thus, Austin suggested naming secondary linguistic functions behind these acts as “illocutionary force”.The speaker may change or modify the latter (strengthens or weakens) depending on the circumstances of the production of the statement. Since the educational learning process is a fertile field of communication, this research paper was a practical procedural field for raising the following problem: How does modifying the illocutionary force contribute to the success of the communication process between the teacher and the learner inside the classroom?
مقال
Keywords: القوة الإنجازيّة , تعديل , تعليميّة; illocutionary force, modification, educational, linguistic illocutionary